Quality-of-life and health utility scores for common cancers in China: a multicentre cross-sectional survey. (October 2016) - Shi, Ju-Fang; Huang, Hui-Yao; Guo, Lan-Wei; Shi, Dian; Gu, Xiu-Ying; Liang, Han; Wang, Le; Ren, Jian-Song; Bai, Ya-Na; Mao, A-Yan; Liu, Guo-Xiang; Liao, Xian-Zhen; et al.
Abstract: Background: The measurement of quality-adjusted life-years (QALYs) forms a key component of cost–utility evaluation in cancer intervention; however, detailed data for utility weights by cancer type and health status are still scarce both in China and other regions. The aim of this study was to systematically evaluate utility scores in relation to the most common six cancers in China in 2012 (lung, breast, colorectal, oesophageal, liver, and stomach cancer). Methods: As a part of a Screening Program in Urban China (CanSPUC) supported by the central government of China, we undertook a cross-sectional survey in 13 provinces across China from 2013 to 2014. Two generic instruments, EQ-5D (EuroQol 5-dimensions) and SF-12 (12-item Short Form Health Survey), and a cancer-specific instrument, FACTs (Function Assessment of Cancer Therapy) were applied. 46 394 participants were interviewed in five groups: general population (n=11 699, group A), individuals who had attended single cancer screening (n=11 805, group B), individuals who had attended multiple screenings (n=6838, group C), patients with precancerous lesions (n=1942, group D), and patients with cancer (n=14 110, group E). All participants had no psychosis and provided written consent to participate in the study. The survey was approved by the Institutional Review Board of the Cancer Hospital of Chinese Academy of Medical Sciences. Findings: The EQ-5D utility scores were 0·96 (95% CI 0·96–0·96) for group A, 0·94 (0·94–0·94) for group B, 0·94 (0·94–0·94) for group C, 0·85 (0·84–0·86) for group D, and 0·77 (0·77–0·77) for group E. Cancer-specific analysis showed that EQ-5D utility scores were 0·77 (0·76–0·78) for lung cancer, 0·78 (0·77–0·79) for breast cancer, 0·75 (0·74–0·76) for colorectal cancer, 0·75 (0·74–0·76) for oesophageal cancer, 0·80 (0·79–0·81) for liver cancer, and 0·76 (0·75–0·77) for stomach cancer. The utility scores for cancer at different clinical stages also differed; for example, the scores for patients with breast cancer were estimated as 0·79 (0·77–0·80) at stage I, 0·79 (0·78–0·80) at stage II, 0·77 (0·76–0·79) at stage III, and 0·69 (0·65–0·72) at stage IV. Compared with data from EQ-5D, results from SF-12 on differences among subgroups seemed narrower; for example, the utility score among the six cancers ranged from 0·60 to 0·62. Interpretation: These data will be applied to future cost–utility evaluation on various cancer screening strategies in China, and could contribute more precise evaluation of burden of disease related to disability-adjusted life-years globally. Funding: The National Health and Family Plan Committee of China.